Faktor-faktor yang mempengaruhi fertilitas wanita pekerja pada rumah tangga miskin di Kabupaten Muaro Jambi (Study Kasus Desa Tantan Kecamatan Sekernan Kabupaten Muaro Jambi) - Abdul Wahab; Junaidi Junaidi; Jaya Kusuma Edi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2018)
The purpose of the study was to analyze income, child costs, working hours of first marriage age and education level towards family fertility in Tantan Village, Sekernan District, Muaro Jambi Regency. The data used is the primary data analysis. Method used in this study qualitative descriptive analysis and quantitative analysis using analytical tools namely multiple linear regression. Based on the simultaneous test, all variables are female income, costs or expenses, working hours, marriage age, level of education together on fertility in Tantan Village, Sekernan District, Muaro Jambi Regency. If partially tested the variables that have contributed are the income of women, the age of marriage and recent education have a significant effect on fertility in the village of Tantan Sekernan District, Muaro Jambi Regency, while the cost and work hours variables have no significant effect on fertility in Tantan Village Sekernan District Muaro Jambi.